86.7k views
2 votes
3 + 5p − 12 = 2p + 12

1 Answer

4 votes

Answer:

p=7

Explanation:

Let's solve your equation step-by-step.

3+5p−12=2p+12

Step 1: Simplify both sides of the equation.

3+5p−12=2p+12

3+5p+−12=2p+12

(5p)+(3+−12)=2p+12(Combine Like Terms)

5p+−9=2p+12

5p−9=2p+12

Step 2: Subtract 2p from both sides.

5p−9−2p=2p+12−2p

3p−9=12

Step 3: Add 9 to both sides.

3p−9+9=12+9

3p=21

Step 4: Divide both sides by 3.

3p

3

=

21

3

p=7

Hope this helps have an amazing day!!

User Frank Nwoko
by
4.9k points